The Impact of Basel II on Operational Risk Management and Its Effects on the Financial Performance of Cambodian Banks - Pijeijesda, Phan (Digital Repository of Theses, 2025)
This study investigates the effect of Basel II principles on operational risk management within Cambodia's commercial banking sector. It centres on assessing the impact of Basel II implementation on risk management frameworks and financial stability in Cambodian banks. The primary research question examined whether adopting Basel II guidelines led to enhanced operational risk management practices among these institutions. To carry out a multi-level comparative analysis of Cambodia’s national banking system, a quantitative research design for studying several primary data sources was implemented in this research. Such sources originated primarily from annual financial statements, regulatory documents, and financial reports from commercial banks. The findings from the secondary data addressed the level of conformity and adherence to Basel II principles within those financial institutions. The study identified different degrees of adherence to Basel II principles by commercial banks based on secondary data. The study describes banks' challenges in implementing the Basel II principles (for example, technical problems and resource shortages). Additionally, this provided information on weaknesses in risk management practices and continuous barriers to the complete implementation of Basel II. This provides critical information, particularly concerning the complexity aspects of adopting Basel II by Cambodian banks. A complete understanding of the challenges faced by these organizations in alignment with the Basel II guidelines was achieved by examining the financial reports and the regulatory documents. The research revealed how incorporating Basel II pillars facilitated compliance and improved risk. These findings are essential for policymakers, regulators, and banking institutions that want to improve their operational risk management framework, strengthening financial stability in Cambodian banks. In addition, this study suggested opportunities for future research by looking into how to overcome the implementation barriers associated with successfully assimilating the Basel II provisions in developing world markets.